Differential sandwich theorems for p-valent functions associated with generalized multiplier transformations - R. M. El-Ashwah; M. K. Aouf; A. Shamandy; S. M. El-Deeb (Le Matematiche, 2013)
In this paper, we obtain some applications of theory of differential subordination, superordination and sandwich results involving an operator.